Marginal distortion of metal-ceramic restorations during the porcelain firing procedure. - (:unkn) unknown (My University, 1993)
The fit of a metal-ceramic casting deteriorates during the firing of a porcelain facing. Although many factors have been reported as the cause of these distortion phenomena, studies of marginal distortion associated with firing metal-ceramic restorations have yielded mixed results. The effect of firing cycles on distortion of a metal-ceramic coping was examined on 0.5 mm thick palladium-copper copings with shoulder marginal finish lines. It was found that the distortion produced in the first stage of firing was greater than at other stages. The marginal distortion seen on the porcelain veneered margin was not significantly different from the distortion on the non-veneered margin. These two results demonstrate that thermal contraction stresses due to porcelain contraction are probably not the primary cause of coping distortion. The internal surfaces of the copings were examined for contamination with porcelain particles and porcelain contamination was detected with an energy dispersive spectrometer analysis. The distortion produced during the porcelain veneering procedure was due to porcelain contamination on the internal surfaces of the copings. A convenient method is necessary to remove porcelain from the internal surfaces of completed restorations.